Towars a chemical reagents and residues management at the teaching laboratories of the Chemistry School of the Universidad Nacional - Benavides Benavides, Ana Cristina (2012)
The academic activities carried out at the School of Chemistry make indispensable to develop actions oriented toward the consolidation of a reagent and residue management system, especially in the teaching laboratories. The project “Management of reagents and residues in the teaching laboratories of the School of Chemistry” works under the Green Chemistry values which designs products and chemical processes that reduce or eliminate the use and production of dangerous substances, to benefit the environment. With a preventive vision, a change from the  laboratory practices is looked to select those with less environmental impact. Additionally, residue quantification is made and its management protocols are developed for each practice. The project has several stages: diagnose, action implementation, student, teacher and administration personnel training and evaluation during the process and at the end of it. The article describes methodological aspects of the project operation emphasizing on reagent and residue quantification through flow diagrams.